Comparative effectiveness of two psychological techniques in the management promiscuity among adolescents in Ibadan (2003)
The study was designed to investigate the effect of covert self-control and assertiveness training in the management of promiscuity as a vital risk factor in the transmission of sexually transmitted infections and human immunodeficiency virus and acquired immune deficiency syndrome (STIs/HIV/AIDS). A pre- and post-test experimental- control group design was employed. Three' local government areas (LGAs) out of the five in Ibadan metropolis, were selected by simple random sampling, and used for the study. One school was selected from each LGA similarly for the two treatment groups and for the control group respectively with forty promiscuous students in each group. The two experimental groups were exposed to a twenty week treatment while the control group received no treatment. Both the treatment programmes were effective in reducing promiscuity in the adolescents. Covert self-control was found to be more effective than assertiveness training. Commendation was received for the free but value-base of the training by the students. Based on the findings, it was recommended that family life education should be implemented in the secondary schools in such a way as to meet the specific value base needs and to adequately control promiscuity among the school children.